Modification of electrical properties of silicon dioxide through intrinsic nano-patterns. (16th May 2018) - Majee, Subimal; Barshilia, Devesh; Banerjee, Debashree; Kumar, Sanjeev; Mishra, Prabhash; Akhtar, Jamil
Abstract: The inherent network of nanopores and voids in silicon dioxide (SiO2 ) is generally undesirable for aspects of film quality, electrical insulation and dielectric performance. However, if we view these pores as natural nano-patterns embedded in a dielectric matrix then that opens up new vistas for exploration. The nano-pattern platform can be used to tailor electrical, optical, magnetic and mechanical properties of the carrier film. In this article we report the tunable electrical properties of thermal SiO2 thin-film achieved through utilization of the metal-nanopore network where the pores are filled with metallic Titanium (Ti). Without any intentional chemical doping, we have shown that the electrical resistivity of the oxide film can be controlled through physical filling up of the intrinsic oxide nanopores with Ti. The electrical resistivity of the composite film remains constant even after complete removal of the metal from the film surface except the pores. Careful morphological, electrical and structural analyses are carried out to establish that the presence of Ti in the nanopores play a crucial role in the observed conductive nature of the nanoporous film.